Los determinantes de la inversión privada en Colombia en el siglo XXI (2020)
This paper presents an analysis of the determinants of investment in the XXI century, taking into account the figures taken from the Penn World Table from the years 1993 to 2017 in order to verify the impact of some variables when taking decisions of the private investment in Colombia. Several economists and thinkers who have carried out studies on the determinants of investment observe and conclude that a model that explains this behavior is the economic accelerator model, where the growth of the economy is taken into account in the formation of private investment; observing that higher GDP growth, higher profits for companies and greater attractiveness for future investors. To determine the importance of these determinants of private investment in Colombia for the XXI century, some economic variables are taken as reference, such as the Gross Domestic Product (GDP), capital stock (K), total-factor productivity (TFP), human capital (HC), public sector expenditures (G), rate of real wages (W), dummy variable (EP) and, interest rate (DTF). Once the econometric estimates are made, we observe statistical significance in the variables proposed in the Kalecki model, for this reason it can be concluded that in the 21st century this model continues being effective in the analysis of the determinants of investment, as presented in this paper.